Wellbeing integrated learning design framework: a multi-layered approach to facilitating wellbeing education through learning design and educational practice - Colla, Rachel H.; Mossman, Lara H. (Frontiers in Education, 2023)
The interest in wellbeing education has risen dramatically as we emerge from a global pandemic and examine what is needed to address the lingering impacts in education. Of course, the need for wellbeing education was apparent long before this, driven by a need to mitigate the growing mental health challenges faced by our youth. Indeed, there is a substantial body of evidence for the impact of such education on students in primary through to tertiary settings. However, little is known about how we are 'educating the educators' to facilitate wellbeing through their curriculum and educational practices. This goes beyond the topics or content of wellbeing education to focus more on how we create enabling environments for wellbeing to emerge in our educational practices. This article proposes a Wellbeing Integrated Learning Design (WILD) Framework to address this gap. We outline the central tenets of the WILD framework, including the underpinning theoretical principles and systems approach that guided the development. Practical examples are provided to demonstrate how the framework can be applied in preparing experienced educators to build enabling environments in their own context. We reflect on the insights gained in trialing the approach in an education faculty in a large Australian university and explore the opportunities to refine the framework further to support its replication in other educational settings. This is a provisional file, not the final typeset article promotion (Lo Moro et al., 2020). Many have argued that educational systems are well placed to implement a health promotion or primary prevention approach (